THE WAY CHINESE-DESCENDENT MOTHERS TEACH CHINESE CULTURE AND THE PRESERVED TRADITIONS IN INDONESIAN-CHINESE MULTICULTURAL FAMILY: A REFLECTION THROUGH THE JOY LUCK CLUB BY AMY TAN - Pratiwi, Amalia; Sili, Surya; Wati, Erna (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2017)
AbstractSince The Joy Luck Club mainly focuses on Chinese culture, it is acknowledged by people around the world that Chinese culture is rich with the values and history which influences every slide of world history. Although Chinese people are recently residing far away from mainland China, the cultural values they have learned before it will be remained within themselves. To uphold the cultural values and traditions within a Chinese-descendent family, the role of mother is needed. However, since most of the Chinese-descendent families live in multicultural neighborhood with the assimilated cultures—like Indonesia—it is unknown whether the Chinese cultural values and traditions are being preserved or not. This study is focused on the way Chinese-descendent mothers teach the Chinese culture and the preserved traditions of Chinese culture within the family. The mothers from The Joy Luck Club represent the role of Chinese-descendent mother in teaching the children the cultural values. These figures are reflected through the mothers in the two cities of Indonesia, Tarakan and Samarinda, as the representation. There are similarities and differences from the mothers from the novel and the two cities in Indonesia in nurturing the children with their cultural values. It comes from the way each mother teaches their cultural values, especially in teaching integrity and filial piety to the children with the mothers’ own method. Several Chinese cultures and traditions are mentioned and still preserved by the family, both in the novel and inside the Indonesian-Chinese mothers’ families. The Lunar New Year and Moon Festival are the examples of the preserved traditions within the family. The results of these studies will show how valuable the cultural values and traditions are and this study will give a further comprehension in preserving the cultural values within a family. Key words: Chinese culture, Indonesian-Chinese, multicultural, The Joy Luck Club, Amy Tan  AbstrakThe Joy Luck Club berfokus pada kebudayaan Cina yang terkenal dengan kekayaan nilai luhur serta sejarahnya yang mempengaruhi sejarah dunia. Meskipun masyarakat Cina saat ini banyak yang bertempat tinggal di luar Republik Rakyat Cina (RRC), nilai budaya mereka dapatkan tetap terjaga. Untuk menjaga nilai kebudayaan dan tradisi di dalam keluarga berketurunan Cina, peran seorang ibu sangat dibutuhkan. Akan tetapi, karena sebagian besar keluarga berketurunan Cina tinggal di lingkungan multikultur dengan budaya yang telah terasimilasi—seperti Indonesia—kita tak mengetahui apakah nilai budaya dan tradisi yang telah dijaga tersebut masih bisa dilestarikan atau tidak. Penelitian ini berpusat pada cara para ibu berketurunan Cina mengajarkan nilai budaya Cina serta mencari tahu apa saja nilai kebudayaan Cina serta tradisi yang masih terjaga di dalam keluarga mereka. Para ibu dari novel The Joy Luck Club merepresentasikan peran mereka dalam mengajarkan nilai kebudayaan serta tradisi tersebut. Mereka akan dibandingkan dengan para ibu yang berasal dari dua kota di Indonesia, yaitu kota Tarakan dan Samarinda, sebagai contoh penelitian. Ada beberapa persamaan dan perbedaan yang didapatkan melalui para ibu dari novel dan dari kedua kota di Indonesia dalam mendidik anak-anaknya dengan nilai budaya tersebut. Hal itu tercermin dari cara setiap ibu mengajarkan nilai integritas dan berbakti kepada yang tua dengan cara mereka masing-masing. Ada beberapa nilai budaya dan tradisi Cina yang disebutkan dan masih dilestarikan oleh keluarga besar mereka, baik dari novel maupun dari dalam keluarga para ibu Indonesia-Cina. Perayaan Tahun Baru Imlek dan Sembahyang Bulan adalah beberapa dari sekian banyak tradisi yang masih terjaga di dalam keluarga Indonesia-Cina. Hasil penelitian ini akan menunjukkan betapa berharganya suatu nilai kebudayaan serta tradisi yang dijalankan serta memberikan pemahaman dalam menjaga budaya dan tradisi di dalam sebuah keluarga. Kata kunci: kebudayaan Cina, Indonesia-Cina, multikultur, The Joy Luck Club, Amy Tan